2022
DOI: 10.1002/jev2.12254
|View full text |Cite
|
Sign up to set email alerts
|

Release of VAMP5‐positive extracellular vesicles by retinal Müller glia in vivo

Abstract: Cell-cell interactions in the central nervous system are based on the release of molecules mediating signal exchange and providing structural and trophic support through vesicular exocytosis and the formation of extracellular vesicles. The specific mechanisms employed by each cell type in the brain are incompletely understood. Here, we explored the means of communication used by Müller cells, a type of radial glial cells in the retina, which forms part of the central nervous system. Using immunohistochemical, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 188 publications
(165 reference statements)
0
9
0
Order By: Relevance
“…In the recent years, considering its low immunogenicity, high biocompatibility, and targeting ability, exosome has attracted much attention and its application in treating retinal diseases has been investigated 18–20 . Valerie Demais et al and our work revealed that exosome from Müller cells played an important role in retina cellular communication 21,22 . In addition, the mesenchymal stem cell‐derived exosome (MSC‐exo) exerts a neuroprotective effect on the injured retina 23,24 .…”
Section: Introductionmentioning
confidence: 61%
See 1 more Smart Citation
“…In the recent years, considering its low immunogenicity, high biocompatibility, and targeting ability, exosome has attracted much attention and its application in treating retinal diseases has been investigated 18–20 . Valerie Demais et al and our work revealed that exosome from Müller cells played an important role in retina cellular communication 21,22 . In addition, the mesenchymal stem cell‐derived exosome (MSC‐exo) exerts a neuroprotective effect on the injured retina 23,24 .…”
Section: Introductionmentioning
confidence: 61%
“…[18][19][20] Valerie Demais et al and our work revealed that exosome from Müller cells played an important role in retina cellular communication. 21,22 In addition, the mesenchymal stem cell-derived exosome (MSC-exo) exerts a neuroprotective effect on the injured retina. 23,24 Here, we investigated whether the certain angiogenic inhibition factors in LECs could be secreted into Lec-exo and attenuate abnormal ocular neovascularization.…”
Section: Introductionmentioning
confidence: 99%
“…2F ). Of note, proteins of organelles that are not related to exosomes and extracellular vesicles in general, such as laminin B1 (LMNB1, nucleus), ribosomal protein S6 and L7 (RSP6, RPL7, ribosome), Golgi matrix protein 130 (GM130, Golgi), carlticulin (CARL, ER) and others [ 49 ], [ 50 ], were not amongst the detected proteins ( Supplementary Table 1 ), highlighting the lack of contaminants and further validating the enrichment of the described brain-derived preparation in exosomes. Moreover, tissue expression analysis pinpointed the hippocampus, brain and brain cortex as the top tissues of origin, further verifying the source-specificity of the isolated ExE-EVs ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…EV are nanosized endogenous cell-to-cell communication vehicles that selectively encapsulate and transport molecular cargo including DNA, proteins and regulatory RNA such as microRNA (miRNA), to shape the biology of recipient cells (Isola & Chen, 2017;Mathieu et al, 2019;Yuana et al, 2013). Work by Kalargyrou et al (2021) demonstrated that in the healthy retina, photoreceptors endogenously released EV to selectively target and communicate with Müller glia (Kalargyrou et al, 2021), while Demais et al (2022) also reported a strong Müller-derived contribution of EV in the retina (Demais et al, 2022). In the brain, bidirectional transfer of EV cargo between neurons and astrocytes has also been shown to influence neuronal morphology and synaptic homeostasis, as well as modulate gliotic states (Ahmad et al, 2022;Ogaki et al, 2021;Schnatz et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…( 2021 ) demonstrated that in the healthy retina, photoreceptors endogenously released EV to selectively target and communicate with Müller glia (Kalargyrou et al., 2021 ), while Demais et al. ( 2022 ) also reported a strong Müller‐derived contribution of EV in the retina (Demais et al., 2022 ). In the brain, bidirectional transfer of EV cargo between neurons and astrocytes has also been shown to influence neuronal morphology and synaptic homeostasis, as well as modulate gliotic states (Ahmad et al., 2022 ; Ogaki et al., 2021 ; Schnatz et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%